2018
DOI: 10.1093/cid/ciy044
|View full text |Cite
|
Sign up to set email alerts
|

As-Needed Vs Immediate Etoposide Chemotherapy in Combination With Antiretroviral Therapy for Mild-to-Moderate AIDS-Associated Kaposi Sarcoma in Resource-Limited Settings: A5264/AMC-067 Randomized Clinical Trial

Abstract: NCT01352117.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
45
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(50 citation statements)
references
References 32 publications
(31 reference statements)
4
45
0
Order By: Relevance
“…The first (ClinicalTrials.gov identifier: NCT01352117 ) was a prospective, randomized, phase III trial to evaluate the role of early versus delayed oral etoposide in people with mild-to-moderate KS who were initiating ART. 18 The study enrolled 192 participants—93% from SSA—and although the primary outcome did not differ between arms, time to KS progression ( P = .021), KS immune response inflammatory syndrome ( P = .003), and KS response ( P = .003) favored the early chemotherapy arm. Additional analyses of associations between early chemotherapy and KS immune response inflammatory syndrome and early KS progression are ongoing, 19 as are studies of baseline prevalence of KSHV inflammatory cytokine syndrome among enrolled participants.…”
Section: Hivam Trials In Ssamentioning
confidence: 99%
“…The first (ClinicalTrials.gov identifier: NCT01352117 ) was a prospective, randomized, phase III trial to evaluate the role of early versus delayed oral etoposide in people with mild-to-moderate KS who were initiating ART. 18 The study enrolled 192 participants—93% from SSA—and although the primary outcome did not differ between arms, time to KS progression ( P = .021), KS immune response inflammatory syndrome ( P = .003), and KS response ( P = .003) favored the early chemotherapy arm. Additional analyses of associations between early chemotherapy and KS immune response inflammatory syndrome and early KS progression are ongoing, 19 as are studies of baseline prevalence of KSHV inflammatory cytokine syndrome among enrolled participants.…”
Section: Hivam Trials In Ssamentioning
confidence: 99%
“…However, the question remains which signs or symptoms of KS are predictive of KS mortality. In addition to TIS staging predictors, previous studies from both high and low income settings have found that pulmonary involvement, 11 woody edema, 22 low BMI, 26 low hemoglobin, 26 low albumin, 25 older age, 23 decreased performance status, 23,25 and positive HHV-8 DNA to be predictive of mortality. 6,27 The linkage of staging criteria with outcomes has recently been performed in the pediatric KS literature in Malawi, but has not yet been performed for the adult KS population in sub-Saharan Africa during the treat-all era.…”
Section: Ks Staging At Time Of Diagnosismentioning
confidence: 99%
“…Upon initiation of cART, KS can also progress, possibly triggered by, or exacerbated by a KS immune reconstitution inflammatory syndrome (IRIS) [10]. AIDS-KS continues to have a high mortality rate in sub-Saharan Africa [11] and is still associated with morbidity and mortality in the US among HIV-infected patients [12].…”
Section: Introductionmentioning
confidence: 99%